Antibody-mediated protection against respiratory syncytial virus in children. - Coindy,EL; Efstathiou,C; Talwar,S; Moureau,A; Vernhes,C; Openshaw,PJM; Thwaites,RS; PROMISE,investigators (Eur Respir Rev, 2024)
Respiratory syncytial virus (RSV) is a major global pathogen, causing lower respiratory tract disease in at-risk populations including young children. Antibodies form a crucial layer of protection from RSV disease, particularly in immunologically naïve infants. Such antibodies are derived from the mother via transplacental transfer and breast milk, but may be particularly low in high-risk infants such as those born preterm. Maternally derived antibodies can now be supplemented by the administration of anti-RSV monoclonal antibodies, while a rising wave of maternal and paediatric vaccine strategies are approaching. The implementation of these prophylactics may profoundly decrease the healthcare burden of RSV. In this article, we review the role of antibody-mediated immunity in protecting children from RSV. We focus on maternally derived antibodies as the main source of protection against RSV and study factors that influence the scale of this transfer. The role of passive and active prophylactic approaches in protecting infants against RSV are discussed and knowledge gaps in our understanding of antibody-mediated protection against RSV are identified.